Genetic divergence in conilon coffee - Fonseca, Aymbiré Francisco Almeida da; Sediyama, Tocio; Cruz, Cosme Damião; Sakaiyama, Ney Sussumu; Ferrão, Maria Amélia Gava; Ferrão, Romário Gava; Bragança, Scheilla Marina (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the genetic divergence between 32 clones of three clonal varieties of conilon coffee, to identify the most dissimilar for the establishment of programs of directed crosses. Genetic divergence was evaluated by multivariate procedures: generalized Mahalanobis distance, the grouping optimization method of Tocher and the technique of canonical variables. Seven characteristics were evaluated in one trial conducted in Marilândia, ES, Brazil. Genotypes ES 92, ES 25 and ES 22 are the most divergent; the last two are the most appropriate for crossing and to obtain hybrids of improved performance by using genetic divergence for good productive performance.